Three-dimensional seismic velocity structure in the Sichuan basin, China - Wang, Maomao (2018)
We present a new three‐dimensional velocity model of the crust in the eastern margin of the Tibetan Plateau. The model describes the velocity structure of the Sichuan basin and surrounding thrust belts. The model consists of 3‐D surfaces representing major geologic unit contacts and faults and is parameterized with Vp velocity‐depth functions calibrated using sonic logs. The model incorporates data from 1166 oil wells, industry isopach maps, geological maps, and a digital elevation model. The geological surfaces were modeled based on structure contour maps for various units from oil wells and seismic reflection profiles. These surfaces include base Quaternary, Mesozoic, Paleozoic, and Proterozoic horizons. The horizons locally exhibit major offsets that are compatible with the locations and displacements of important faults systems. This layered, upper crustal 3‐D model extends down to 10–15 km depth and illustrates lateral and vertical variations of velocity that reflect the complex evolution of tectonics and sedimentation in the basin. The model also incorporates 3‐D descriptions of Vs and density for sediments that are obtained from empirical relationships with Vp using direct measurements of these properties in borehole logs. To illustrate the impact of our basin model on earthquake hazards assessment, we use it to calculate ground motions and compare these with observations for the 2013 Lushan earthquake. The result demonstrates the effects of basin amplification in the western Sichuan basin. The Sichuan CVM model is intended to facilitate fault systems analysis, strong ground motion prediction, and earthquake hazards assessment for the densely populated Sichuan region.